2009
DOI: 10.1369/jhc.2009.954610
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Angiopoietin-1 and Tie2 Immunoreactivity in Rodent Ependyma and Adjacent Blood Vessels Suggests Functional Relationships

Abstract: , Illinois (PK) S U M M A R Y Angiopoietin-1 (Angpt1; previously Ang-1) participates in vascular maintenance and remodeling. In the current study, we investigated the distribution of Angpt1 protein in rat brain. We detected Angpt1 immunoreactivity (IR) in cerebral blood vessels, cuboidal ependyma, and tanycytes, which are specialized hypothalamic bipolar ependymal cells. We also evaluated patterns of IR of endothelium-specific receptor tyrosine kinase 2 (Tie2, the receptor for Angpt1). Tie2 IR was present in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
(30 reference statements)
1
2
0
Order By: Relevance
“…This is in accordance with previous reports showing that sources of Ang-1 include perivascular astrocytes, endothelial cells, ependymal cells, and the choroid plexus (Acker et al, 2001;Nourhaghighi et al, 2003;Ward et al, 2005;Ohab et al, 2006;Tonchev et al, 2007;Fukuhara et al, 2008;Horton et al, 2010). Moreover, Ang-1 mRNA was detected in SVZ from adult mice (Liu et al, 2009), and we showed that proliferating DCXpositive neuroblasts and EGFR-positive progenitors express Tie-2.…”
Section: Discussionsupporting
confidence: 93%
“…This is in accordance with previous reports showing that sources of Ang-1 include perivascular astrocytes, endothelial cells, ependymal cells, and the choroid plexus (Acker et al, 2001;Nourhaghighi et al, 2003;Ward et al, 2005;Ohab et al, 2006;Tonchev et al, 2007;Fukuhara et al, 2008;Horton et al, 2010). Moreover, Ang-1 mRNA was detected in SVZ from adult mice (Liu et al, 2009), and we showed that proliferating DCXpositive neuroblasts and EGFR-positive progenitors express Tie-2.…”
Section: Discussionsupporting
confidence: 93%
“…ANGPT1 is expressed in astrocytes, neurons, pericytes and endothelial cells but is predominantly expressed by astrocytes in the brain 4346 . Angiopoietin-1 has previously been shown to reduce infarct size by stabilizing endothelial cell integrity, reducing blood brain barrier permeability, and promoting angiogenesis 4749 .…”
Section: Discussionmentioning
confidence: 99%
“…This ligand–receptor binding triggers pericyte proliferation and migration along the newly formed vascular sprout which stabilizes the newly formed vessel [ 21 , 22 , 23 ]. Other pathways known to be involved in endothelial-pericyte crosstalk include angiopoietin/Tie2 [ 24 , 25 ] transforming growth factor (TGF) superfamily signaling [ 26 , 27 ] and vascular endothelial growth factor (VEGF) [ 18 , 28 ].…”
Section: Pericytes – Mural Cells Of Capillaries That Play Roles In Anmentioning
confidence: 99%